Statistical analysis of winning percentages in Japanese professional baseball using the Wins above Replacement indicator - Shino Shimizu; Yasuhiro Suzuki (PLoS ONE, 2026)
This study examines a previously unexplored concept in the field of sabermetrics. By employing a novel correction that accounts for player position differences, it investigates the impact of the designated hitter (DH) system on team wins in Japanese professional baseball using the Wins above Replacement metric. We applied this innovative correction to Pacific League data from 2014 to 2023, accounting for positional differences in player contributions. Our results indicate no significant difference in the correlation coefficients between team average wins above replacement (WAR) and winning percentage under conditions including and excluding the DH position, suggesting that the DH system does not substantially impact team performance. These findings offer a nuanced understanding of the DH system’s role in baseball strategy and team dynamics.